2019
DOI: 10.1051/matecconf/201925502013
|View full text |Cite
|
Sign up to set email alerts
|

Automated Valve Fault Detection Based on Acoustic Emission Parameters and Artificial Neural Network

Abstract: Reciprocating compressor is one of the most popular classes of machines use with wide applications in the industry. However, valve failures in this machine often results unplanned shutdown. Therefore, the effective valve fault detection technique is very necessary to ensure safe operation and to reduce the unplanned shutdown. This paper propose an artificial intelligence (AI) model to detect valve condition in reciprocating compressor based on acoustic emission (AE) parameters measurement and artificial neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Following experimental verification, we observed that better results can be obtained by setting the learning rate to 0.1. The sigmoid function was used uniformly for activation functions in all models [ 16 – 18 ]. The optimization algorithm is a mathematical model that uses the idea of iteration to approximate the optimal solution to the problem.…”
Section: Methodsmentioning
confidence: 99%
“…Following experimental verification, we observed that better results can be obtained by setting the learning rate to 0.1. The sigmoid function was used uniformly for activation functions in all models [ 16 – 18 ]. The optimization algorithm is a mathematical model that uses the idea of iteration to approximate the optimal solution to the problem.…”
Section: Methodsmentioning
confidence: 99%
“…Ali et al [63,64] investigated fault detection technologies based on artificial intelligence (AI) and AE signals. They proposed two AI models to detect the valve condition in a reciprocating compressor based on several AE signals using SVM and ANN [63,64]. In the literature [65], the ANN and SVM models were trained and evaluated for detection of valve faults in an RC.…”
Section: Fault Diagnosis Based On Acoustic Emission (Ae)mentioning
confidence: 99%